Archetype X: Visible and Invisible Otherness. (2nd October 2018) - Nevin Welsh, Sarah
Abstract : This article applies Jungian psychology to the film Get Out (2017), written and directed by Jordan Peele. It examines American culture, race, and racism issues through the conceptual lenses of complexes, archetypes, and personal myth. The movie is organized into a series of chapters exploring psychological, racial complexes: the complex of being the objectified other, the complex of not being other enough, and the complex of otherness and annihilation . The article then considers personal myth and the presence of invisible otherness in the lives of both Jung and Peele. The author places emphasis on the necessity and responsibility of the other as a disrupter and developer of personal and cultural individuation, and proposes the development of an archetype of otherness through the arts, Archetype X. The naming of this new archetype opens a way for the marginalized to begin to be seen, to create a home in which to place themselves and to belong.